Jim Altman, SJSU student preparing a solar energy frame. - Lee, Russ (photographer):::Creator::::::::::::
Written on verso: "SJSU student Jim Altman prepares a solar energy frame for the installation of water piping. The solar panels will occupy the spaces between the studs. (PHOTO BY: Russ Lee)"